Lexical-functional syntax - Bresnan, Joan (Malden, MA : Chichester, West Sussex : Wiley-Blackwell, 2015)
'Provides both an introduction to LFG and a synthesis of major theoretical developments in lexical-functional syntax over the past few decades'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Grammar, Comparative and general -- Syntax; Lexical-functional grammar; LANGUAGE ARTS & DISCIPLINES / Linguistics / Syntax; Grammar, Comparative and general -- Syntax; Lexical-functional grammar; Electronic books; Electronic books; Electronic books